Women's empowerment based on local potential: Processing aloe vera into functional beverages as a featured MSME product for PCA Kuwarasan, Kebumen - Dyah Puji Astuti; Diah Astutiningrum; Umi Laelatul Qomar; Juni Sofiana; Sumarni Sumarni (Community Empowerment, 2026)
The potential of aloe vera as a functional food material with high economic value remains underutilized at the community level, particularly among women's groups. This community service program aims to enhance the capacity of members of the Aisyiyah Branch Leadership (PCA) in Kuwarasan, Kebumen Regency, in processing aloe vera into value-added and competitive functional beverages to serve as a featured local MSME product. The implementation methods included counseling on aloe vera utilization, technical training on product processing and packaging, production practice mentoring, and evaluation of program outcomes. The results demonstrated an increase in participants' knowledge and skills regarding the aloe vera processing workflow, ranging from raw material preparation and beverage production to final packaging. Furthermore, participants showed improved self-confidence and readiness to develop micro-enterprises based on local resources. This initiative contributes directly to strengthening women's roles in family economic empowerment.